Multiple Imaging and Surgical Characteristics in Cardiac Metastasis from Undifferentiated Uterine Sarcoma - Hiroka Sasahara; Shoichiro Yatsu; Hideki Wada; Eiryu Sai; Soshi Moriya; Suguru Miyazaki; Kan Kajimoto; Manabu Ogita; Satoru Suwa (Case Reports in Cardiology)
Although cardiac metastasis of malignant tumors has often been reported, undifferentiated uterine sarcoma (UUS) is a rare and aggressive uterine tumor. Thus, little is known of the UUS as a primary site of cardiac metastasis. We report a case of a 66-year-old woman, with a history of uterine myoma for 30 years, who was hospitalized with a large uterine tumor and cardiac masses. Although we investigated cardiac masses using imaging modalities, such as ultrasound, cardiac computer tomography, and magnetic resonance imaging, it was challenging to determine the masses as metastasis or thrombi. Cardiac masses were removed by surgery to assess the tissue characteristics and were later identified as tumors due to their appearance. Then, pathological findings revealed that UUS spreads to the right ventricle. We attempted chemotherapy after surgery; however, the disease progressed very quickly and the patient died on the 49th day of admission. In this report, we described the case of a patient with a difficult diagnosis and rapid disease progression of cardiac metastasis from UUS.